Mastering Microsoft Sharepoint Foundahion 2010 - Callahan (Indianapolis, Indiana Wiley, 2011)
This book provides step by step coverage of topics system administrators need to know including creating and administreting sites site collections web applications security and disaster recovery gain insight into using and managing web parts listes and libraries
12
Keywords: Microsoft Office Sharepoint server; Web Servies